The Policy of Bruening Government and the Position of Social-Democracy of Prussia During the 30-ies of XX Century - Папенко, Н. (Київський національний університет імені Тараса Шевченка, 2011)
The author serveys the dynamics of the imperial policy of Bruening government and attitude to it by Social Democratic coalition government of Prussia during the period of Weimar Republic in Germany.

Розглянуто динаміку імперської політики уряду Г.Брюнінга часів Веймарської республіки в Німеччині та ставлення до неї коаліційного соціал-демократичного уряду Пруссії.
Політика уряду Г. Брюнінга та позиція соціал-демократів Пруссії упродовж 30-х років ХХ ст.
Keywords: уряд Брюнінга; Веймарська республіка; соціал-демократичний уряд Пруссії; Brüning government; Weimar Republic; Social Democratic government of Prussia